Infarct Volume-Based Subgroup Selection in Acute Ischemic Stroke Trials. Issue 5 (May 2015) - Kufner, Anna; Wouters, Anke; Bracoud, Luc; Laage, Rico; Schneider, Armin; Schäbitz, Wolf-Rüdiger; Hermier, Marc; Thijs, Vincent; Fiebach, Jochen B.
Abstract : Background and Purpose—: We investigated whether hyperintensities with a diameter of at least 3, 3.5, and 4 cm and visible on at least 3 slices on diffusion-weighted imaging enables patient selection with an infarct volume of ≥15 mL. Methods—: Consecutive acute stroke patients were screened for the AXIS2 trial and examined according to a standardized magnetic resonance imaging protocol in 65 sites. Diffusion-weighted lesion diameters were measured and compared with volumetric assessments. Results—: Out of 238 patients, 86.2% (N=206) had infarct diameter of at least 3 cm. Volumetric assessments showed infarct volume of ≥15 mL in 157 patients. A cut-off value of 3 cm led to 96.8% sensitivity and 33.3% specificity for predicting lesion volume of ≥15 mL. Analogously, a 3.5 cm cut-off led to 96.8% sensitivity and 50.6% specificity and a 4 cm cut-off led to 91.7% sensitivity and 61.7% specificity. Conclusions—: Lesion diameter measures may enable multicentric patient recruitment with a prespecified minimal infarct volume. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00927836.